Eco-literacy in Science Learning: A Review and Bibliometric Analysis - Iman Kadarisman; Indarini Dwi Pursitasari (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Eco-literacy plays an important role in learning awareness about protecting the environment. Ecoliteracy needs to be given to children early to instill basic environmental preservation behaviors. There has been a decline in environmental quality due to low awareness of eco-literacy. This study aims to review bibliometric literature on applying eco-literacy-based learning to increase student awareness of the importance of protecting the surrounding environment. The literature review was taken from articles obtained using the Publish or Perish (PoP) application from 2017 to 2022 and obtained 67 articles. The articles are then analyzed using VOSviewer software to map and look for research gaps that are still possible to be researched. Some topics provide research opportunities, including